Integrative taxonomy to clarify the identity of Anastrepha dissimilis Stone, 1942 (Diptera: Tephritidae), with an illustrated key to the species of Anastrepha pseudoparallela group recorded on passion fruit (Passiflora sp.) in Brazil - Araújo, Alexandre Santos (2022)
The fruit flies of the genus Anastrepha Schiner comprise a group of phytophagous Diptera. Some species are pests of fruticulture, as they use economically significant fruits as a nutritional resource for the larval stage. Taxonomically, the genus is divided into multiple groups of species, according to morphological and molecular evidence. The pseudoparallela group comprises 31 described species, 11 of which are registered in Brazil. Species of the pseudoparallela group mainly infest passion fruits (Passiflora spp.). However, in Brazil, the taxonomic knowledge of these species is still limited. So far, there is no taxonomic key for identifying the species of this group recorded in passion fruit in Brazil. Furthermore, most study of species in this group has focused on species that attack fruits of commercial species of Passiflora, such as Anastrepha consobrina and A. pseudoparallela. Among the poorly known species of the pseudoparallela group, is Anastrepha dissimilis Stone, 1942, which has a wide distribution in Brazil, occurring in 20 states. Morphological comparisons of the A. dissimilis paratype from Bonito, Pernambuco, Brazil with the holotype collected in Plaisance, Haiti, suggest that more than one species is confused under a single nominal species. Therefore, this research aims to carry out a taxonomic study of Brazilian populations of A. dissimilis using an integrative approach and to produce an illustrated key to the Brazilian species of the pseudoparallela group recorded in passion fruit. The specific objectives of this thesis plan are: (1) to compare the morphology of the aculeus of A. dissimilis from multiple localities; (2) to carry out a morphometric study of the wing, aculeus, and mesonotum of Brazilian populations of A. dissimilis, using linear and geometric analysis; (3) to perform a molecular study of Brazilian populations of A. dissimilis, using the subunit I of the mitochondrial gene Cytochrome Oxidase (COI); (4) to develop an illustrated key to the species of the pseudoparallela group recorded in passion fruit in Brazil; and (5) to enhance the collection of the Museu de Entomologia Luiz de Queiroz (MELQ) of the Escola Superior de Agricultura Luiz de Queiroz (ESALQ/USP) with the specimens collected and identified in the study. Morphological and molecular analyses of specimens from different localities in Brazil, that would be identified as A. dissimilis using the current identification key, suggested that they are A. chiclayae Greene. Furthermore, the morphometric study showed considerable morphological variation among several populations, suggesting the existence of at least two morphospecies. Thus, in this study, the integrative taxonomic approach allowed us to register, for the first time, the occurrence of A. chiclayae in Brazil. In addition, a checklist of species of the A. pseudoparallela group registered in passion fruit in Brazil was prepared using data from the literature. Finally, an illustrated taxonomic key for identifying these species was developed.